Dampak Pemakaian Diapers Terhadap Kegagalan Toilet Training Pada Anak Usia 3 Tahun Di TPA Masagena Makassar - Zulfikar Marsiding; Andi Resvi (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
Toddler ageg children are the golden age because the development of toddler-age children, namely 1-3 years old, experiences very rapid growth and development, so that if at this toddler age they experiences obstacles in growth and development, it will have a big impact on the childs life in the future. One the big tasks for toddler is toilet training, so that children are not dependent on using diapers. The aim of this research is to find out the general pictures of the impact of using diapers on toilet training failure of 3 year old children an the Masagena Daycare Centre. The type of research used is non-experimental quantitative research using a cross sectional design, namely by studing the dynamics of the correlation between risk factor dan effect, using an observational approach or collecting data at on time (pont time approac). This research want to know the effect of using diapers (as a riskfactor) on the success of toilet training for children aged 3 years (as an effect, where riskfactors and effect are observed and measured simultaneously at the same time). Based on the research results, diapers are very dominant in influencing the failure of a childs toilet training is compared with the childs own readiness.